Islamic Branding as a Competitive Advantage Strategy in Transformative Islamic Education - Wathon, A; Sulistyorini, Sulistyorini; Sujianto, Agus Eko (LP2M STIT Palapa Nusantara, 2026)
This study explores Islamic branding as a strategic approach to achieving competitive advantage in Islamic educational institutions in the contemporary global and digital era. Increasing competition among educational providers has encouraged institutions to develop distinctive identities that emphasize not only academic excellence but also ethical and spiritual values. This study aims to analyze how Islamic values are integrated into marketing frameworks, leadership practices, stakeholder engagement, and digital transformation to strengthen institutional branding. A qualitative approach with a conceptual and literature-based design was employed, focusing on recent scholarly works published between 2024 and 2025. Data were collected through a systematic literature review and analyzed using thematic analysis techniques. The findings indicate that Islamic branding, when integrated with the 7P marketing mix, enhances institutional credibility, public trust, and stakeholder satisfaction. Leadership, particularly religious leadership represented by kyai, plays a central role in shaping institutional legitimacy and brand identity. Furthermore, digital transformation and artificial intelligence provide new opportunities for branding innovation, although ethical and infrastructural challenges remain significant. The study concludes that Islamic branding must move beyond symbolic representation and be deeply embedded in governance, pedagogy, and institutional culture to achieve sustainable competitive advantage. This study contributes to the theoretical development of Islamic educational management and offers practical recommendations for policymakers and educational leaders in strengthening value-based institutional branding.